A Review Study of Bio-Psycho-Social Challenges and Interventions for Women During their Perinatal Period - Khushi Pruthi; Achintya Kothiyal; Praney Kumar; Smriti Sethi (International Journal of Children, 2024)
Pregnancy causes women to face dynamic and sudden changes in their body and psyche, and sometimes they might as well feel dissociated or separated from the journey. Even though they mentally adapt to the pregnancy, they require constant support at all levels to face the challenges during this crucial period. The goal of the current research is to examine the bio-psycho-social challenges and interventions for women during their perinatal period. The main objectives were to focus and study on how transition takes place with regards to women biologically, psychologically, spiritually and professionally during the perinatal period, to understand how women deal with identity crisis and self-doubt during and after pregnancy, to propose interventions for healthy perinatal care for both mother and their children. Researchers have shown that every woman cope with imbalances due to hormones that lead to changes in body and mind that certainly changes their lifestyle. Researchers also studied that mothers who face anxiety, severe mood swings, cold feet and disruption in her self-esteem. Other people around the women, if not are supportive, might view her as overdramatic, over-reactive and someone who is using pregnancy as an excuse to get over stuff. This review paper applies a secondary method of research to reach its conclusion; More than 30 studies from previous years were taken into account while forming the discussion and conclusion. Many past studies indicate the involvement of partner, parental relationship, environment around women, motherhood transition, work life of women, teratogens and psychological neglect during the timeframe of pregnancy. They provide a broadened perspective to the objectives and help to understand the causes and consequences of the above-mentioned effectively. The research evidence further highlights that pregnancy leads to significant changes at physical, mental, emotional and social aspects of every woman &s life. Thus, it is recommended that women should be helped and supported all the time by family and improvised health care services if need be i.e. therapeutic interventions, etc. Future implications of studying women in the perinatal period can help with increasing the awareness / psychoeducation of maternal and infant health outcomes to the general public.
Keywords: Hormonal imbalances; Maternal health; perinatal period; pregnancy support; psychoeducation; therapeutic interventions